Successful conception in a 34-year-old lupus patient following spontaneous pregnancy after autotransplantation of cryopreserved ovarian tissue. (April 2019) - Chehab, G; Krüssel, J; Fehm, T; Fischer-Betz, R; Schneider, M; Germeyer, A; Suerdieck, M B; Kreuzer, V; Liebenthron, J
Premature gonadal failure is a common problem in patients with systemic lupus erythematosus (SLE) when gonadotoxic therapies are applied. The preservation of gonadal function and fertility is of great importance to many predominantly young SLE patients. Some fertility preservation methods are well established and well known, whereas others are considered more cautiously. In particular, the cryopreservation of ovarian tissue is a rarely chosen fertility preservation option for SLE patients of (pre)fertile age. We report the first case of successful conception and pregnancy of an SLE patient after autotransplantation of cryopreserved ovarian tissue. A 26-year-old SLE patient decided to undergo cryopreservation of ovarian tissue when receiving cyclophosphamide for lupus nephritis. Tissue removal, preparation, cryopreservation and quality control was performed, as described, according to current state-of-the-art techniques. After 6 years of being in remission using azathioprine and belimumab, her ovarian tissue was autotransplanted because of premature ovarian failure, diagnosed at the age of 32, and a wish to conceive. She conceived spontaneously 8 months later, having a diamniotic-dichoriotic twin pregnancy. The children were born prematurely due to preterm premature rupture of membranes in the 32nd week of gestation; mother and children are doing very well 8 months later. We regard the procedure to be an option worth consideration for our predominantly young SLE patients.